A. 7⁸÷7⁵-11² B. 3⁴.3-5¹⁶÷5¹³+2023⁰.12² C. 4³÷4-2².3+5².3 D. 2015⁰.14+3².2-5¹⁰÷5⁸
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(=\dfrac{5}{7}\left(\dfrac{5}{11}+\dfrac{2}{11}-\dfrac{14}{11}\right)=\dfrac{5}{7}\cdot\dfrac{-7}{11}=-\dfrac{5}{11}\)
b: \(=\dfrac{12}{7}\left(19+\dfrac{5}{8}-15-\dfrac{1}{4}\right)=\dfrac{12}{7}\cdot\left(4+\dfrac{3}{8}\right)\)
\(=\dfrac{12}{7}\cdot\dfrac{35}{8}=\dfrac{3}{2}\cdot5=\dfrac{15}{2}\)
c: \(=\dfrac{2}{15}-\dfrac{2}{15}\cdot5+\dfrac{3}{15}=\dfrac{2}{15}\cdot\left(-4\right)+\dfrac{3}{15}=\dfrac{-8+3}{15}=\dfrac{-5}{15}=-\dfrac{1}{3}\)
d: \(=\dfrac{4}{9}\left(19+\dfrac{1}{3}-39-\dfrac{1}{3}\right)=\dfrac{4}{9}\cdot\left(-20\right)=-\dfrac{80}{9}\)
- Tính giá trị biểu thức:
a) (2/5 x 25/29) + (3/5 x 25/29)
= (50/145) + (75/145)
= 125/145
b) (5/2 x 3/7) - (3/14 : 6/7)
= 15/14 - (3/14 x 7/6)
= 15/14 - 1/2
= (30/28) - (14/28)
= 16/28
= 4/7
c) (15/4 : 5/12) - (6/5 : 11/15)
= (15/4 x 12/5) - (6/5 x 15/11)
= 180/20 - 90/55
= 9 - 18/11
= (99/11) - (18/11)
= 81/11
= 7 4/11
- Tính giá trị biểu thức:
a) (2/3) + (20/21 x 3/2 x 7/5)
= 2/3 + (60/210)
= 2/3 + 2/7
= (14/21) + (6/21)
= 20/21
b) (5/17 x 21/32 x 47/24 x 0)
= 0
c) (11/3 x 26/7) - (26/7 x 8/3)
= (286/21) - (208/21)
= 78/21
= 3 9/21
= 3 3/7
- Tìm x:
a) (25/8) : x = 5/16
=> (25/8) x (16/5) = x
=> 4 = x
b) x + (7/15) = 6/15
=> x = (6/15) - (7/15)
=> x = -1/15
c) x : (28/49) = 7/12
=> x x (49/28) = 7/12
=> x = (7/12) x (28/49)
=> x = 1/2
- Tìm x:
a) 6 x x = (5/8) : (3/4)
=> 6x = (5/8) x (4/3)
=> 6x = 20/24
=> 6x = 5/6
=> x = (5/6) / 6
=> x = 5/36
câu,b,không,đủ,thông,tin,nhan,bạn.
a)\(\dfrac{-6}{11}:\left(\dfrac{3}{5}.\dfrac{4}{11}\right)=\dfrac{-5}{2}\)
b)\(\dfrac{7}{12}+\dfrac{5}{12}:6-\dfrac{14}{30}=\dfrac{67}{370}\)
c)\(\left(\dfrac{4}{5}+\dfrac{1}{2}\right):\left(\dfrac{3}{13}-\dfrac{8}{13}\right)=-\dfrac{169}{50}\)
d)\(\left(\dfrac{2}{3}-\dfrac{1}{4}+\dfrac{5}{11}\right):\left(\dfrac{5}{12}+1-\dfrac{7}{11}\right)=\dfrac{115}{103}\)
1:
a: =23/27-11/17+4/27+28/17
=23/27+4/27+28/17-11/17
=1+1=2
b: \(=\dfrac{2}{3}\cdot\left(\dfrac{7}{9}+\dfrac{2}{9}\right)-\dfrac{2}{9}\)
=2/3-2/9
=6/9-2/9
=4/9
c: \(=\dfrac{11}{5}\cdot\dfrac{7}{3}-\dfrac{1}{3}\cdot\dfrac{11}{5}\)
=11/5(7/3-1/3)
=11/5*2
=22/5
d: \(=\dfrac{3}{2}\cdot\dfrac{4}{3}\cdot...\cdot\dfrac{2024}{2023}=\dfrac{2024}{2}=1012\)
e: \(=\dfrac{1}{2}\cdot\dfrac{2}{3}\cdot...\cdot\dfrac{2022}{2023}=\dfrac{1}{2023}\)
b: \(27D=3^{14}+3^{17}+...+3^{2024}\)
\(\Leftrightarrow26D=3^{2024}-3^{11}\)
hay \(D=\dfrac{3^{2024}-3^{11}}{26}\)
c: \(25E=-5^4-5^6-...-5^{1002}\)
\(\Leftrightarrow24E=-5^{1002}+5^2\)
hay \(E=\dfrac{-5^{1002}+5^2}{24}\)
\(a,\dfrac{6}{11}+6+\dfrac{5}{7}=\dfrac{42+462+55}{77}=\dfrac{559}{77}\)
\(b,\dfrac{9}{8}\times\dfrac{3}{12}:\dfrac{5}{9}=\dfrac{9}{8}\times\dfrac{3}{12}\times\dfrac{9}{5}=\dfrac{243}{480}=\dfrac{81}{160}\)
\(c,\dfrac{8}{7}:4+2=\dfrac{8}{7}\times\dfrac{1}{4}+2=\dfrac{8}{28}+2=\dfrac{2}{7}+2=\dfrac{16}{7}\)
\(d,\dfrac{3}{5}+4:\dfrac{6}{4}=\dfrac{3}{5}+4\times\dfrac{4}{6}=\dfrac{3}{5}+\dfrac{8}{3}=\dfrac{49}{15}\)
a)\(-\dfrac{2}{5}.\dfrac{4}{7}+\dfrac{-3}{5}.\dfrac{2}{7}+\dfrac{-3}{5}\)
=\(-\dfrac{2}{5}.\dfrac{4}{7}+\dfrac{3}{7}.\dfrac{-2}{5}+\dfrac{-3}{5}\)
=\(-\dfrac{2}{5}.\left(\dfrac{4}{7}+\dfrac{3}{7}\right)+\dfrac{-3}{5}\)
=\(\dfrac{-2}{5}.1+\dfrac{-3}{5}\)
=\(-\dfrac{2}{5}+\dfrac{-3}{5}\)
=\(-\dfrac{5}{5}\) = -1
\(\dfrac{5}{9}.\dfrac{14}{17}+\dfrac{1}{17}.\dfrac{5}{9}+\dfrac{2}{9}+\dfrac{5}{12}\)
=\(\dfrac{5}{9}.\left(\dfrac{14}{17}+\dfrac{1}{17}\right)+\dfrac{2}{9}+\dfrac{5}{12}\)
=\(\dfrac{5}{9}.\dfrac{15}{17}+\dfrac{2}{9}+\dfrac{5}{12}\)
=\(\dfrac{25}{51}+\dfrac{2}{9}+\dfrac{5}{12}\)
=\(\dfrac{691}{612}\)
a) 11/12 + 5/6 x 3/2 - 2/3
= 11/12 + 15/12 - 2/3
= 26/12 - 2/3
= 26/12 - 8/12
= 18 /12 = 3/2
b) 4/9 : 4/6 x 3/4 +5/3
= 4/9 x 6/4 x 3/4 + 5/3
= 2/3 x 3/4 + 5/3
= 6/12 + 5/3
= 6/12 + 20/12
= 26/12 = 13/6
c) 5/7 : 11/14 : 15/22 x 3/5
= 5/7 x 14/11 x 22/15 x 3/5
= 10/11 x 22/15 x 3/5
= 4/3 x 3/5 = 20/15 = 4/3
a. \(\dfrac{11}{12}+\dfrac{5}{6}\)x\(\dfrac{3}{2}-\dfrac{2}{3}\) \(=\)\(\dfrac{11}{12}+\dfrac{5}{4}-\dfrac{2}{3}=\dfrac{11}{12}+\dfrac{15}{12}-\dfrac{8}{12}=\dfrac{11+15-8}{12}=\dfrac{18}{12}=\dfrac{3}{2}\)
b. \(\dfrac{4}{9}:\dfrac{4}{6}\)x\(\dfrac{3}{4}+\dfrac{5}{3}\) \(=\dfrac{4}{9}:\dfrac{1}{2}+\dfrac{5}{3}=\dfrac{8}{9}+\dfrac{5}{3}=\dfrac{8}{9}+\dfrac{15}{9}=\dfrac{8+15}{9}=\dfrac{23}{9}\)
c. \(\dfrac{5}{7}:\dfrac{11}{14}:\dfrac{15}{22}\)x\(\dfrac{3}{5}\) \(=\dfrac{10}{14}:\) \(\dfrac{11}{14}:\dfrac{15}{22}\)x\(\dfrac{3}{5}\) \(=\dfrac{10}{11}\)\(:\dfrac{15}{22}\)x\(\dfrac{3}{5}\) \(=\dfrac{20}{22}:\dfrac{15}{22}\)x\(\dfrac{3}{5}\) \(=\dfrac{4}{3}\)x\(\dfrac{3}{5}=\dfrac{4}{5}\)
a: =7^3-11^2
=343-121=222
b: =3^5-5^3+144
=243-125+144
=243+19
=262
c: =4^2-4*3+25*3
=63+16=79
d: =14+9*2-25
=-11+18=7